Recurrent Breast Cancer Following Modified Radical Mastectomy and Risk Factors - Mutlak, Noufel Sh.; Al-Mukhtar, Ramiz; Al-Dawoodi, Nabeel S.; Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: - Recurrent breast cancer is cancer that comes back following initial treatment. Risk factors of recurrence are lymph node involvement, larger tumor size, positive or close tumor margins, and lack of radiation treatment following lumpectomy, younger age and inflammatory breast cancer. Objective: Asses the rate of recurrence for early breast cancer in Iraqi female patients, in relation to certain risk factors. Patients and methods: A prospective study was conducted on 100 consecutive female patients, with stage I and stage II breast cancer treated by mastectomy and axillary dissection by the same team. Patients were assessed postoperatively every three months and recurrences were detected by physical examination and ultrasound of the bed of mastectomy and axilla. Statistical correlation using univariant analysis between recurrence rate and certain associated variables was done. Results: Recurrence rate was found to be 13%. It was more common among both young (20-29) years &the (40 – 49 ) years age groups which was 16.7%. Most of recurrences (61.6%) occurred (within 12_19 months) after surgical treatment. Statistically significant associations were found between recurrence and the latency period between first complaint and surgical management, the grade of the tumor, the size of primary tumor, and the number of lymph nodes involved. There was no statistically significant association between the type of adjuvant therapy and the incidence of local recurrence. Conclusions: the rate of recurrence after modified radical mastectomy is relatively high in our study. The same known risk factors related to the stage, grade and delay of treatment were detected, and close follow up especially at the first 20 months after surgery is recommended.